2021
DOI: 10.1080/10717544.2021.1879313
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanism of matrine in treatment of COVID-19 combined with liver injury by network pharmacology and molecular docking technology

Abstract: The aim of the present study was to investigate the pharmacological mechanism of matrine in treatment of COVID-19 combined with liver injury. Potential targets related to matrine, COVID-19 and liver injury were identified from several databases. We constructed PPI network and screened the core targets according to the degree value. Then, GO and KEGG enrichment were carried out. Molecular docking technology was used to verify the affinity between matrine and the crystal structure of core target protein. Finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In summary, using network pharmacology we may identify the pathways that drug delivery carriers induced signaling and potent enzyme activity. The bioinformatics tool can provide an efficient approach to expedite the biochemical analysis to target the potent signaling and applying the drug delivery platform especially at nanoscale for enhanced efficiency (Liu et al, 2021 ), by the dual function of interface effect and herbzyme effect.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, using network pharmacology we may identify the pathways that drug delivery carriers induced signaling and potent enzyme activity. The bioinformatics tool can provide an efficient approach to expedite the biochemical analysis to target the potent signaling and applying the drug delivery platform especially at nanoscale for enhanced efficiency (Liu et al, 2021 ), by the dual function of interface effect and herbzyme effect.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified tumor protein p53 ( TP53 ) hub-high traffic TF in the turquoise module, with an important role in the pathogenesis of COVID-19 ( 415 ). Moreover, in an animal model of COVID-19, ALI in the infected group was associated with an increase in TP53 expression ( 416 ). Besides, 1 study reported that an increase in the expression of TP53 led to the induction of apoptosis in PBMCs and thus reduced their frequencies in COVID-19 patients ( 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mortality rate among hospitalized COVID-19 patients strongly correlated with the autoimmunity level to annexin A2 [ 10 ], suggesting its importance in SARS-CoV-2 pathogenicity [ 11 ]. Matrine was shown to directly target annexin A2 by a photo-affinity labeling approach [ 12 ], while very recent network pharmacological studies suggested that matrine may also have varying targets in cellular signaling pathways [ 13 , 14 , 15 ]. Oxymatrine (OMAR) and sophoridine (SPD, Scheme 1 ) are matrine-type alkaloids isolated from S. flavescens Ait with promising biological activities [ 16 , 17 ], including antiviral activity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%